Sargassum muticum Hydrothermal Extract: Effects on Serum Parameters and Antioxidant Activity in Rats - Elena M. Balboa; Rosendo Millán; Herminia Domínguez; Cristina Taboada (Applied Sciences, 2019)
Sargassum muticum was processed by hydrothermal extraction under previously optimized non-isothermal conditions (up to 187 °C). The alginate free crude hydrolysate was further concentrated by ultrafiltration, operating in diafiltration mode to produce an extract (SmE) enriched in the fucoidan and the phlorotannin fractions and with low mineral content and antiradical capacity equivalent to that of Trolox. In order to explore the potential of this concentrated product for food or feed additive, the in vivo antioxidant potential was assessed. Male Sprague−Dawley rats were fed SmE dissolved in distilled water at doses of 0.5, 1.0 or 2.0 g kg−1, administered via an intragastric tube daily for three weeks. The weight and organ gain was not significantly affected in the different groups in relation to the control group fed a standard diet. Serum glucose was significantly lowered in the groups receiving the higher SmE doses, liver GPx levels were reduced and liver TBARS levels decreased in rats administered the extract, but no effect on SOD activity in either liver or erythrocytes was observed.